Rabbit Dental Abnormalities: Investigation of Conformational Risk Factors in a Pedigree Rabbit Population - Maria A. Jackson; Michaela Betts; Joanna Hedley; Charlotte C. Burn (Animals)
Lop-eared and brachycephalic conformations have inconsistently been associated with dental abnormalities in pet and rescue rabbit populations. We investigated conformational risk factors for dental abnormalities in a pedigree population where conformation could be confirmed. Otoscopic oral examination was performed on breeder-volunteered pedigree rabbits at British Rabbit Council shows and studs. Multivariable models were used for risk factor analysis of 14 possible dental disease signs. In 435 rabbits examined, 68.28% showed no incisor abnormalities and 55.40% showed no cheek teeth abnormalities. Lop-eared rabbits had higher odds than erect-eared rabbits for ocular discharge (odds ratio [OR]: 4.034, p = 0.007) but not for any dental abnormalities. Erect-eared rabbits showed higher odds of reacting to incisor examination than lop-eared rabbits (OR: 1.666, p = 0.003). Brachycephaly showed no associations with dental abnormalities, whilst more dolichocephalic rabbits had increased odds of cheek teeth step or wave mouth (OR: 1.394, p = 0.004). Other conformational and signalment-related risk factor results were mixed. Brachycephaly showed no significant predisposition to dental abnormalities, and the clinical relevance of predisposition to ocular discharge in lop-eared rabbits is unclear. Conformation appears less important than husbandry factors for preventing rabbit dental disease. Generalising the results to companion rabbits is not advised due to husbandry and population differences.